Correlation of physical aging and glass transition temperatures in ultrathin polystyrene films supported on SiO2. (16th September 2021) - Sharma, Tulika; Nishio, Yoshiaki; Tamano, Yuichiro; Sato, Harumi; Takahashi, Isao
Abstract: This study examined the effects of the aging temperature ( T age ) on structural relaxation in ultrathin-supported polystyrene (PS) films with thickness ~0.2Rg. X-ray reflectivity and differential scanning calorimetry were used to evaluate the glass transition temperature ( T g ) of ultrathin PS and bulk PS, respectively. The ultrathin films in their confined state showed anomalous thickness relaxation behaviors that could be classified into three types: (1) T age ≤ 60 °C, a slow increase in thickness with time and a decrease in relaxation magnitude with temperature; (2) 70 °C ≤ T age ≤ 110 °C, a slow decrease in thickness with time and an increase in relaxation magnitude with temperature; (3) T age > 110 °C, an increase in thickness with time due to dewetting of PS films deposited on SiO 2 . Such an interesting relaxation behavior can arise from the enhanced dynamics at the surface and reduced mobility at the interface inherent in ultrathin-supported films. Two distinct T g s peculiar to ultrathin films were confirmed. The lower T g has not been reported for supported PS films. The relaxation summarized above revealed a strong correlation with the T g values . The de Gennes modified sliding motion model was applied to explain the correlation with relaxation dynamics. Graphical abstract: Image 1 Highlights: Slow relaxation in the ultrathin PS films is investigated using X-Ray Reflectivity. Relaxation behavior is observed in a wide range of temperature, from 30 °C to 140 °C . PS films with h o ~0.2Rg exhibit an anomalous thickness relaxation. Presence of two distinct two T g s in ultrathin PS films below T g bulk . Strong correlation of thickness relaxation behavior with measured T g values.